Pore structure and pertinent physical properties of nanofibrillated cellulose (NFC)-based foam materials. (1st December 2018) - Li, Jinbao; Cheng, Rui; Xiu, Huijuan; Zhang, Meiyun; Liu, Qiang; Song, Te; Dong, Huiling; Yao, Bin; Zhang, Xuefei; Kozliak, Evguenii; Ji, Yun
Highlights: Freeze-drying temperature and solid content affect NFC foam microstructure. Layered pore and interlayer pillared structure occurred at 3%–5% NFC content. Higher NFC content and lower freeze-drying temperature resulted in smaller pores. Interlamellar wall thickness decreased with temperature until disappeared at −196 °C. Foam mechanical strength and thermal conductivity depend on density and porosity. Abstract: Nanofibrillated cellulose (NFC)-based foam materials have broad prospects in replacing traditional foams, due to its facile natural biodegradation. This study addressed the relationship between the foam preparation process parameters and resulting pore structure. An aqueous NFC suspension was freeze-dried while adding an organic solvent, ethanol, to adjust the curing process. The effects of the solid content and freeze-drying temperature on the microstructure and mechanical stability as well as heat transfer performance of the produced NFC-based foam were investigated. The foam obtained at a 3%–5% solid content featured a well-defined lamellar and interlayer pillar support structure. With an increase in the solid content, the average wall thickness increased whereas the average pore area decreased. Yet the pore density increased with the pore distribution becoming non-uniform. With a decrease in freezing temperature, the wall thickness decreased (with no wall structure at −196 °C) but the pore density increased, with the pores being distributed more uniformly. The foam mechanical strength and thermal conductivity were found to be linked to porosity. The foam material had the most suitable mechanical and thermal insulation properties when prepared with a 5% solid content at a freeze-drying temperature of −55 °C.